THE EFFICACY OF POULTRY MANURE ON THE GROWTH AND YIELD OF TWO CAPSICUM SPECIES: CAPSICUM ANNUUM AND CAPSICUM FRUTESCENS (FUDMA JOURNAL OF SCIENCES, 2023)
This study was carried out to determine the efficacy of poultry manure on the growth and yield of Capsicum annuum and Capsicum frutescens. The treatments include; 0g, 2g, 4g, 6g and 8g of poultry manure per pots containing 3kg of soil. Each treatment had three replicates. The treatments were arranged in a complete randomized block design. Data collected on the growth and yield parameters showed that both species were favoured in terms of growth and yield parameters by the high concentration of poultry manure. The control, which signifies no application of the manure had, generally, the lowest values in terms of growth and yield parameters for both species
Keywords: Poultry manure, growth and yield parameters, capsicum species, pepper